Perbandingan Kualitas Lks Ipa Biologi Yang Diterbitkan Oleh PT. Percada, PT. Pratama Mitra Aksara, Usaha Makmur Solo Dan CV. Putra Kertonatan - RETNAWATI, MITA; Dra. Suparti, M.Si., Dra. Suparti, M.Si (2016)
National Education Minister Regulation No. 41 of 2007 regulating the learning process that requires planning for educators to develop learning resources, one of which is the student worksheet. This study aims to determine the suitability analyze worksheets with KTSP, determine the level of activation of students and percentage levels of exercises on worksheets Biology Class VII Semester 2015/2016 school year a publish of Surakarta. The study used four worksheets from different publishers, namely Suplemen Bahan Ajar, Prestasi Pustaka, Intensif and STAR This type of research is descriptive qualitative data collection techniques nontes that uses observation sheets. Data were analyzed using percentages and index the degree of activation. The results obtained that Quality Suplemen Bahan Ajar and STAR Instructional Materials are included in the category of being to the level of conformity with KTSP, while LKS Achievement and Intensif Reader included in the low category to the level of conformity with the KTSP. Suplemen Bahan Ajar and Prestasi Pustaka included in the medium category and Intensif and STAR included in the low category. All worksheets are included in the medium category for students on the activation index assessment from all worksheets included in the low category for the index activation of students in the problem. All worksheets have exercises based on cognitive psychomotor and affective charge that has not been proportional.